Airflow management and energy saving potentials at a high-density data center with stepped-like server placement. Issue 14 (14th November 2022) - Yuan, Xiaolei; Liang, Yumin; Pan, Yiqun; Kosonen, Risto; Wang, Yu
ABSTRACT: This paper proposed and introduced an innovative concept of step-like server placement in data centers (DCs), replacing the traditional servers placed on the same vertical plane with step-like server placement. The studied simplified DC model was established based on an actual operating DC. The feasibility and reliability of the simplified model was validated by on-site experimental results. This paper is analyzed two scenarios: the effects of horizontal spacings (0, 0.01, 0.02, 0.03, and 0.04 m) between adjacent servers and with the effect of different supply air temperatures (SATs) (22.5, 23, 23.5, and 24°C) on the rack hotspot. The results show that step-like server placement can effectively enhance the thermal distribution, while the optimum thermal distribution is achieved with the spacing of 0.01 m in case 2. Under this circumstance, the rack hotspot reduced by 2.5°C, while case 2 is selected for further analysis in scenario 2. In scenario 2, the thermal environment in cases 6–8 are totally better than that in case 1 in terms of rack hotspot and temperature distribution. Although there appears another moderate heat accumulation at the top-side, the overall thermal distribution in the case with SAT of 24°C is still better than that in original case. The electricity consumptions of the CRACs can be saved by approximately 146 and 195 kWhr/day with the most optimal configuration.